Pediatric Upper Airway Obstruction - Kelly Levasseur; Kurt Filips (Association of American Medical Colleges, 2015)
Abstract Introduction When a child presents with an upper airway foreign body, a physician may have seconds to minutes to implement proper treatment. We present an actual case of an infant who presented to an adult emergency department with near-complete upper airway obstruction requiring placement of a transtracheal jet ventilation. Methods This is an excellent case to help teach learners how to recognize upper airway foreign body, partial, and complete obstruction and help them develop an algorithm for management. The simulation includes a scenario template, an instructor's guide, a PowerPoint presentation, and other simulation documents. Results Approximately, 40 learners have completed this module during 10 separate sessions. Learners who have participated in this simulation case have given feedback that this case is very helpful for their learning. They feel more comfortable with recognizing upper airway obstruction and placement of the transtracheal jet ventilation. They feel more confident with their management of an upper airway obstruction, and after completing this case, they have an algorithm for management of upper airway foreign bodies. Discussion Many learners did not recognize foreign body aspiration initially and instead thought that the patient had croup and went down that treatment pathway. They quickly recognized that the patient did not get better and had to broaden their differential diagnosis. We noticed that the learners were more confident in their differential diagnosis of stridor in an infant after completing this case.